Thoracic spinal epidural empyema in a cat - Cecco, Bianca Santana de; Santos, Igor Ribeiro dos; Molossi, Francieli Adriane; Dal Pont, Tainah Pereira; Lopes, Bruna Correa; Fett, Rochana Rodrigues; Pavarini, Saulo Petinatti (Brazilian Journal of Veterinary Pathology, 2022)
A 2-month-old male domestic shorthair cat was referred to a private veterinary clinic with a history of dyspnea and inappetence. At the clinical examination, the cat was in poor body condition, with hyperthermia and abdominal distension. No major abnormalities were observed in the thoracic radiographs or abdominal ultrasound. A complete blood count revealed leukocytosis with neutrophilia. Although no clinical diagnosis was made, the cat received support therapy, but went into cardiac arrest and died. The cat was submitted for necropsy and the main gross finding was two white nodules on the ventral surface of the thoracic vertebrae (from T1 to T4). At the cut surface, the nodules were friable and filled with yellow exudate. The epidural space of the thoracic region was filled with yellowish viscous material. Histologically, the vertebrae were partially replaced by abscess formation characterized by a necrotic center with degenerate neutrophils, surrounded by fibrous connective tissue. The epidural space was filled with degenerate neutrophils, necrotic debris, fibrin, and intralesional colonies of gram-negative short rod-shaped to coccobacillary bacteria. Bacteriologic culture yielded Pasteurella multocida. This paper describes the gross, histological, and bacteriological features of a rare case of spinal epidural empyema caused by Pasteurella multocida in a cat.